Glycemic benefits with adherence to testosterone therapy in men with hypogonadism and type 2 diabetes mellitus. (8th March 2021) - Jenkins, Craig R.; Rittel, Alex; Sturdivant, Rodney X.; Wan, Jen; Clerc, Philip G.; Manning, Evan; Jenkins, Lydia M.; Wardian, Jana L.; Graybill, Sky D.
Abstract: Background: While previous studies have demonstrated testosterone's beneficial effects on glycemic control in men with hypogonadism and Type 2 Diabetes, the extent to which these improvements are observed based on the degree of treatment adherence has been unclear. Objectives: To evaluate the effects of long‐term testosterone therapy in A1C levels in men with Type 2 Diabetes Mellitus and hypogonadism, controlling for BMI, pre‐treatment A1C, and age among different testosterone therapy adherence groups. Materials and methods: We performed a retrospective analysis of 1737 men with diabetes and hypogonadism on testosterone therapy for 5 years of data from 2008–2018, isolating A1C, lipid panels, and BMI results for analysis. Subjects were categorized into adherence groups based on quartiles of the proportion of days covered (> 75% of days, 51–75% of days, 26–50% of days and 0–25% of days), with >75% of days covered considered adherent to therapy. Results: Pre‐treatment median A1C was 6.8%. Post‐treatment median A1C was 7.1%. The adherent group, >75%, was the only group notable for a decrease in A1C, with a median decrease of −0.2 ( p = 0.0022). BMI improvement was associated with improved post‐treatment A1C ( p = 0.007). When controlling for BMI, age, and pre‐treatment A1C, the >75% adherence group was associated with improved post‐treatment A1C ( p < 0.001). Discussion: When controlling for all studied variables, testosterone adherence was associated with improved post‐treatment A1C. The higher the initial A1C at the initiation of therapy, the higher the potential for lowering the patient's A1C with >75% adherence. Further, all groups showed some reduction in BMI, which may indicate that testosterone therapy may affect A1C independent of weight loss. Conclusion: Even when controlling for improved BMI, pre‐treatment A1C, and age, testosterone positively impacted glycemic control in diabetes patients with hypogonadism, with the most benefit noted in those most adherent to therapy (>75%).